Kebebasan Beragama dalam Perspektif Deklarasi Universal HAM dan Deklarasi Kairo 1990 - Yusdiandra Alfarishy (IN RIGHT: Jurnal Agama dan Hak Azazi Manusia, 2023)
Abstract: The Universal Declaration of Human Rights and the Cairo Declaration speak of rights and freedoms and place man as noble and dignified. However, there are fundamental differences regarding views, reference materials and the discussion. Universal Declaration of Human Rights is derived from humanistic philosophical thought and departs from the perspective of human interests. At the same time, the Cairo Declaration rests on the view of tawhid and is derived from the texts of Islamic religious teachings. If the Universal Declaration of Human Rights gives a broad understanding of freedom, it is not the case with the Cairo Declaration. Instead of allowing widespread freedom, the Cairo Declaration was intended only to protect Muslims from the threat of incitement to apostasy. The difference is understandable because Universal Declaration of Human Rights makes man his main starting point–where every decision-making process and how to take advantage of freedom is left to (man) as the authoritative rights holder. While on the other hand, the Cairo Declaration views a Muslim as a being who has obligations towards his fellow human beings and the rules of shari'a.Abstrak: Deklarasi Universal HAM dan Deklarasi Kairo bicara soal hak dan kebebasan serta meletakkan manusia sebagai makhluk mulia dan bermartabat. Akan tetapi, ada perbedaan mendasar menyangkut pandangan; materi rujukan; serta pembahasannya. DUHAM bersumber dari pemikiran filsafat humanistik serta bertolak dari pandangan kepentingan manusia, sementara Deklarasi Kairo justru bertumpu pada pandangan ketauhidan dan bersumber dari teks-teks ajaran agama Islam. Jika DUHAM memberi pengertian luas terhadap kebebasan, tidak demikian dengan Deklarasi Kairo. Alih-alih memungkinkan kebebasan yang luas, Deklarasi Kairo justru hanya bermaksud melindungi kepentingan umat Islam dari ancaman hasutan kemurtadan. Perbedaan itu dapat dimengerti, sebab DUHAM menjadikan manusia sebagai titik tolak utamanya–dimana dalam tiap proses pengambilan keputusan dan bagaimana cara memanfaatkan kebebasan diserahkan kepada (manusia) selaku pemegang hak yang otoritatif. Sementara Deklarasi Kairo, memandang seorang muslim sebagai subjek yang tidak hanya memiliki kewajiban serta hubungan dengan sesama manusia tetapi juga terhadap aturan-aturan syari’at.